1998
DOI: 10.1046/j.1525-1497.1998.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS patients’ perspectives on adhering to regimens containing protease inhibitors

Abstract: OBJECTIVE:To gather qualitative data regarding HIV/AIDS patients' perspectives about HIV-1 protease inhibitors (PIs), and about their experiences taking and adhering to regimens containing PIs. DESIGN:Six focus groups of persons under care for HIV were conducted between September and November 1996 regarding participants' knowledge, awareness, experiences when taking, and adherence to antiretroviral regimens containing PIs. An identical discussion guide was used to facilitate all six groups. Focus group proceed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0
7

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 33 publications
3
58
0
7
Order By: Relevance
“…These findings are supported by various studies which reported that forgetting to take a dose as the most commonly seen predictors of poor adherence to therapy [12,16,17].…”
Section: Discussionsupporting
confidence: 74%
“…These findings are supported by various studies which reported that forgetting to take a dose as the most commonly seen predictors of poor adherence to therapy [12,16,17].…”
Section: Discussionsupporting
confidence: 74%
“…• The nature of the regimen (HAART regimen requires strict adherence and schedule of doses affects eating, sleeping, daily routines, social and recreational activities, sex, working life, social relationships, care-giving roles, studying, weight and thereby dominates life) [143][144][145][146][147][148][149][150][151][152] • Type of medication (HAART has frequent doses, high number of pills per day, and off-putting taste, smell, size and shape) 145,146,151,152 • Gender (women more sceptical regarding safety and efficacy of HAART than men, regimen impacts more on women than on men) 142,149,151 • Perceived efficacy of medication [142][143][144][148][149][150][151] • Lay evaluation of medication for efficacy (with HAART subjective rather than objective indicators given more weight) 143,[147][148][149][150] • Adverse effects (with HAART a/effects nasty, impacted on QoL and instilled distrust in medication and led to not taking drugs as prescribed as medication experienced as making you ill rather than better -again, subjective rather than objective indicators more important) [142][143][144][145][146][147][148][149][150][151]…”
Section: Factors Influencing Whether or Not People 'Take Drugs As Prementioning
confidence: 99%
“…• Informal networks/peers could influence either way 142,143 • Acceptance of HIV infection status (accepting it oneself and being able to disclose it to others) 152…”
Section: Factors Influencing Whether or Not People 'Take Drugs As Prementioning
confidence: 99%
See 2 more Smart Citations